Dielectric barrier discharge plasma microbubble reactor for pretreatment of lignocellulosic biomass. Issue 11 (7th September 2018) - Wright, Alexander; Bandulasena, Hemaka; Ibenegbu, Christopher; Leak, David; Holmes, Thomas; Zimmerman, William; Shaw, Alex; Iza, Felipe
Abstract : A novel lignocellulosic biomass pretreatment reactor has been designed and tested to investigate pretreatment efficacy of miscanthus grass. The reactor was designed to optimize the transfer of highly oxidative species produced by dielectric barrier discharge plasma to the liquid phase immediately after generation, by arranging close proximity of the plasma to the gas‐liquid interface of microbubbles. The reactor produced a range of reactive oxygen species and reactive nitrogen species, and the rate of production depended on the power source duty cycle and the temperature of the plasma. Ozone and other oxidative species were dispersed efficiently using energy efficient microbubbles produced by fluidic oscillations. A 5% (w/w) miscanthus suspension pretreated for 3 h at 10% duty cycle yielded 0.5% acid soluble lignin release and 26% sugar release post hydrolysis with accelerated pretreatment toward the latter stages of the treatment demonstrating the potential of this approach as an alternative pretreatment method. © 2018 The Authors. AIChE Journal published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers. © 2018 The Authors. AIChE Journal published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers. AIChE J, 64: 3803–3816, 2018